2013
DOI: 10.1371/journal.pone.0068862
|View full text |Cite
|
Sign up to set email alerts
|

Armed Rollers: Does Nestling’s Vomit Function as a Defence against Predators?

Abstract: Chemical defences against predators are widespread in the animal kingdom although have been seldom reported in birds. Here, we investigate the possibility that the orange liquid that nestlings of an insectivorous bird, the Eurasian roller (Coracias garrulus), expel when scared at their nests acts as a chemical defence against predators. We studied the diet of nestling rollers and vomit origin, its chemical composition and deterrent effect on a mammal generalist predator. We also hypothesized that nestling roll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Our results also showed that the relative success of asynchronous broods varied with local rainfall in the previous month to reproduction, which seems to be another piece of evidence suggesting that food availability is the basis of the found pattern. Rollers mainly feed offspring with arthropods (grasshoppers; Parejo et al 2013) and arthropods abundance is determined in semi-arid areas by previous local rainfall (Illera and Díaz 2006). Therefore, asynchronous broods seem to be favoured in less productive years, when rainfall during the month previous to reproduction is scarce and, hence, when arthropods abundance is likely to be limited.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results also showed that the relative success of asynchronous broods varied with local rainfall in the previous month to reproduction, which seems to be another piece of evidence suggesting that food availability is the basis of the found pattern. Rollers mainly feed offspring with arthropods (grasshoppers; Parejo et al 2013) and arthropods abundance is determined in semi-arid areas by previous local rainfall (Illera and Díaz 2006). Therefore, asynchronous broods seem to be favoured in less productive years, when rainfall during the month previous to reproduction is scarce and, hence, when arthropods abundance is likely to be limited.…”
Section: Discussionmentioning
confidence: 99%
“…However, after clutch completion both sexes participate in incubation and feeding tasks (Cramp and Simmons 1988;Avilés et al 2011). Diet of nestling rollers is exclusively insectivorous, being arthropods the main prey delivered by parents (Avilés and Parejo 1997;Parejo et al 2013), which suggests that climatic factors affecting insect production are likely to affect roller reproductive features.…”
Section: Study Population and Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…In birds, nest predation has promoted the evolution of various morphological, physiological, and behavioural anti-predator adaptations (Martin 1987; Lima 2009; Parejo et al 2013). Potential prey may be able to change the behaviour of a predator, but cavity-nesting birds generally remain hidden, relying on a small cavity entrance as passive nest protection.…”
Section: Introductionmentioning
confidence: 99%
“…(•) indicates that the 95% confidence intervals don't overlap with 0, and (×) indicates that they do species distribution at a local scale. Factors such as nest location, habitat patch composition and presence of conspecifics and/or predators are known to highly affect nest site selection in European Roller Vaclav et al 2011;Parejo et al 2013;Bouvier et al 2014).…”
Section: Effects On Nest Box Occupancymentioning
confidence: 99%